Paradoksy - Tworak, Zbigniew (Filozofia Publiczna i Edukacja Demokratyczna, 2012)
An important part of philosophical thinking are paradoxes. Many of them raise serious problems and are associated with crises of thought and revolutionary advances in the science. This paper is devoted to the notion of paradox and presents a potpourri of paradoxes. I give a very broad interpretation of the term paradox, far broader than will appeal to many logical purists.